Praktik Pungutan Liar (Pungli) di Lingkungan Masyarakat - Goa, Marselinus; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Rabid wild ridge practice once implemented. Its most easily found form is the one that almost occurs in various public places, where we often find the presence of irresponsible members of the public who demand parking money illegally. The action is obviously troubling because it is against the regulations in that the place actually does not collect parking fees from visitors. With this case regulated in the Act, In Article 1 number 64 of Law no. 28 of 2009 mentions the issue of parking levy which is a payment on services or granting of certain permits specifically provided or granted from the local government as in the interest of an individual or body. So this parking clerk can be subject to the law of extortion and intimidation in articles 368-371 of the Criminal Code is part of CHAPTER XXIII of the Criminal Code which contains goods, which are completely or partially belonging to the person himself belonging to another person or so that the person makes a debt or cancels the debt, is punished for extortion with a life imprisonment for nine years In the regulation of area No. III Daerah Pahun Pajak 20 1 which read “Tax Collection prohibited wholesale”.